Development of the Local Food Systems Policy Index (Local Food-EPI+) tool and assessment process to benchmark the implementation of local government policies for creating healthy, equitable and environmentally sustainable food systems - Oriana Ruffini; Chanel Relf; Davina Mann; Miranda R Blake; Amy Carrad; Belinda Reeve; Liza Barbour; Lana Vanderlee; Stefanie Vandevijvere; Gary Sacks (Cambridge University Press, 2024)
Abstract Objective: Local governments have an important role to play in creating healthy, equitable and environmentally sustainable food systems. This study aimed to develop and pilot a tool and process for local governments in Australia to benchmark their policies for creating healthy, equitable and environmentally sustainable food systems. Design: The Healthy Food Environment Policy Index (Food-EPI), developed in 2013 for national governments, was tailored to develop the Local Food Systems Policy Index (Local Food-EPI+) tool for local governments. To incorporate environmental sustainability and the local government context, this process involved a literature review and collaboration with an international and domestic expert advisory committee (n 35) and local government officials. Setting: Local governments. Results: The tool consists of sixty-one indicators across ten food policy domains (weighted based on relative importance): leadership; governance; funding and resources; monitoring and intelligence; food production and supply chain; food promotion; food provision and retail in public facilities and spaces; supermarkets and food sources in the community; food waste reuse, redistribution and reduction; and support for communities. Pilot implementation of the tool in one local government demonstrated that the assessment process was feasible and likely to be helpful in guiding policy implementation. Conclusion: The Local Food-EPI+ tool and assessment process offer a comprehensive mechanism to assist local governments in benchmarking their actions to improve the healthiness, equity and environmental sustainability of food systems and prioritise action areas. Broad use of this tool will identify and promote leading practices, increase accountability for action and build capacity and collaborations.